Penyuluhan Hukum Perlindungan Hak Cipta Film dan Lagu Berdasarkan Undang-undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Yetti, Yetti; Dewi, Sandra; Utama, Andrew Shandy (STMIK Dharmapala Riau, 2021)
Target partners priority issues to be resolved is increased knowledge of high school students in Al-Huda Pekanbaru concerning the legal protection of copyright movies and songs are bought and sold in the form of pirated VCDs by Act No. 28 of 2014 on Copyright. Method of implementation of community service is to use the lecture method, dialogue and discussion. Partner participation in community service activities is by providing time, providing a place, as well as presenting the students as a participant. For the proposer, outcomes that will be achieved is in the form of the publication of scientific articles, as well as teaching material for enrichment courses Intellectual Property Law and can not be separated from the manifestation of Tri Dharma college. The conclusion is that the implementation of community service activities have been 'successfully' implemented and the benefits can be felt directly by the participants, which is to increase the knowledge of students at SMA Al-Huda Pekanbaru concerning the legal protection of copyright movies and songs based on Law Number 28 Year 2014 concerning Copyright. It can be seen from the answers of the participants in the questionnaire given after the implementation of the activities. Of the 32 participants, 98.2% answered have understood. Her advice is preferably routine activities with this theme executed by the target audience is not only the students but also the general public, so that people can know and understand the legal protection of copyright movies and songs based on Law Number 28 Year 2014 on Copyright.